POLA KONSUMSI DAN KETAHANAN PANGAN RUMAH TANGGA NELAYAN DI DESA MAJA KECAMATAN KALIANDA KABUPATEN LAMPUNG SELATAN - Ismah, Khairunnisa; Zakaria, Wan Abbas; Indriani, Yaktiworo (Jurnal Ilmu-Ilmu Agribisnis, 2020)
This research aimed to analyze consumption pattern, food security level, and factors that influence the consumption pattern of household fisherman marker. This research was conducted by survey method. Location of this research was determined purposively in Maja Village, Kalianda District, South Lampung Regency. The amount of research samples of 40 fisherman labor with the respondents in the research were the heads of household and housewives. The data was collected in April-May 2018. Data analysis method used was quantitative analysis and multiple linear regression analysis. The consumption pattern was assessed by non-consecutively the Desirable Dietary Pattern (DDP) score based on the food recall of household consumption for 2x24 hours. The DDP score was calculated from the energy intake of each group of food consumed. The results showed that the number of types of food consumed by fisherman household was 10-13 kinds (62.5%) and the frequency of food consumed by fisherman household is rice. TheDesirable Dietary Pattern (DDP) score of fisherman household was 66.72. The level of food security of fisherman household in Maja Village based on the results of cross classification between the level of energy sufficiency and share of food expenditure could be divided in four categories. There were11 households (27.5%) food resistant, 21 households (52.5%) less food, 4 households (10.0%) vulnerable food, and 4 households (10.0%) food insecure. The factors that influenced household?s consumption patterns at Maja Village were maternal age and household income.Keywords: consumption patterns, fishing households, food security.